Early Diagenesis in the Hypoxic and Acidified Zone of the Northern Gulf of Mexico: Is Organic Matter Recycling in Sediments Disconnected From the Water Column? - Rabouille, Christophe; Lansard, Bruno; Owings, Shannon M.; Rabalais, Nancy N.; Bombled, Bruno; Metzger, Edouard; Richirt, Julien; Eitel, Eryn M.; Boever, Anthony D.; Beckler, Jordon S.; Taillefert, Martial (Frontiers in Marine Science, 2021)
Hypoxia and associated acidification is a growing concern for ecosystems and biogeochemical cycles in the coastal zone. The northern Gulf of Mexico (nGoM) has been experiencing large seasonal hypoxia for decades linked to the eutrophication of the continental shelf by the Mississippi River nutrient discharge. Sediments play a key role in maintaining hypoxic and acidified bottom waters, but the precise understanding of their role is still progressing. During the summer 2017 which hit a record in hypoxic surface area in the nGoM, we investigated 4 sediment stations located on the continental shelf under the influence of the Mississippi-Atchafalaya River System which are differentially influenced by the river input and seasonal hypoxia. Using a coupling between amperometric, potentiometric and voltammetric microprofiling with high-resolution Diffusion Equilibration in Thin-films (DET) profiles, and porewater analysis, we investigated the diagenetic processes in sediments under normoxic, hypoxic and nearly anoxic bottom waters. In addition, we used a time-series of bottom-water dissolved oxygen from May to November 2017 which indicated intense O2 consumption in bottom waters related to organic carbon recycling. At the sediment-water interface, we found that oxygen consumption linked to organic matter recycling was large with diffusive oxygen uptake (DOU) of 8 and 14 mmol m-2 y-1, except when oxygen concentration is near anoxia (5 mmol m-2 y-1). Deeper in the sediment, except at the station located near the river outlet, downcore sulfate decrease in pore waters was limited, with little increase of alkalinity, dissolved inorganic carbon (DIC), ammonium and phosphate suggesting that low oxygen conditions did not favor anoxic diagenesis as could be anticipated. We attributed the low intensity of anoxic diagenesis to a limitation in organic substrate supply possibly linked to the reduction of bioturbation during the hypoxic springs and summer.